2017
DOI: 10.1590/1413-785220172502162204
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anterolateral Ligament of the Knee in Formalin-Embedded Cadavers

Abstract: Objective: To verify the incidence and characterize morphologically the anterolateral ligament of the knee (ALL) in cadaveric samples of the collection of the Laboratory of Anatomy of the Department of Morphology of the Universidade Federal do Espírito Santo. Methods: Dissections and cross sections were performed for mesoscopic analysis of the anterolateral region of 15 knees preserved in 4% formalin solution in order to identify the ALL. Results: After dissection of the skin and subcutaneous tissue of the kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Fardin et al [23] described a dissection technique starting with a section of the ITB 5 cm proximal to the lateral epicondyle of the femur, followed by detachment up to Gerdy’s tubercle in order to identify the articular capsule, the LCL and the tendon of the popliteus muscle. However, in contrast to literature data and evidence of the presence of the ALL is most knees, in none of the 15 specimens studied was the ALL identified properly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fardin et al [23] described a dissection technique starting with a section of the ITB 5 cm proximal to the lateral epicondyle of the femur, followed by detachment up to Gerdy’s tubercle in order to identify the articular capsule, the LCL and the tendon of the popliteus muscle. However, in contrast to literature data and evidence of the presence of the ALL is most knees, in none of the 15 specimens studied was the ALL identified properly.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding its function in knee kinematics is currently being investigated [4, 5]. However, a few studies still report a low ALL visualization rate in dissections [9, 23, 2527]. Those that did not find the ALL were usually performed with techniques that might interfere with proper ALL isolation and on embalmed cadavers [9, 23, 26], which may hinder dissection, regardless of the technique used.…”
Section: Discussionmentioning
confidence: 99%
“…48 Previous studies have reported variable prevalence or identification of the ALL in cadaveric dissections, ranging from 0% to 100%. 8,12,38,45,50,51 Several studies have noted a thickening within the ALC but no distinct anatomic structure in anatomic dissections and MRI studies. 11,21,30 In the current study, a distinct or nondistinct ALL was determined by the presence or absence of a ligamentous structure in the appropriate anatomic location.…”
Section: Discussionmentioning
confidence: 99%
“…34 Anatomic studies of the ALL have shown conflicting results, with a reported prevalence between 0% and 100%. 8,12,38,45,50,51 Histological examination of the ALL has shown ligamentous and capsular organization. 5,11,15 There is a complex relationship among the other anterolateral knee structures, such as the iliotibial band, Kaplan fibers, and anterolateral capsule (ALC), but the structure-function relationship is unknown.…”
mentioning
confidence: 99%
“…Perceptions of anatomy, function, current imaging capabilities, and optimal ways to restore ALL have changed over time and continue to do so today. There is still no consensus among scientists on the anatomy of the ALL, and even its existence is questioned by several anatomical studies [4].…”
mentioning
confidence: 99%